Antibacterial Effects of Brewed Javanese Turmeric (Curcuma xanthorrhiza Roxb.) on Porphyromonas gingivalis Bacteria - Marakata, Ujwalita Manohara; Putranto, Ricky Anggara; Binartha, Ciptadhi Tri Oka (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Javanese turmeric (Curcuma xanthorrhiza Roxb.) contains antibacterial compounds such as flavonoids, saponins, tannins, phenols, triterpenoids, curcuminoids, and quinones, that has potential alternative mouthwash for managing periodontitis, without the side effects of tooth staining and mucosal irritation. This study aims to examine the antibacterial effects of brewed Javanese turmeric against Porphyromonas gingivalis bacteria. This is an in vitro experimental study using a pre-test only group design. Antibacterial testing was conducted using the dilution method with brewed Javanese turmeric at concentrations of 5 grams, 2.5 grams, 1.25 grams, 0.625 grams, and 0.3125 grams. A 0.2% chlorhexidine solution was used as a positive control, and distilled water as a negative control. Data were analyzed using the Post Hoc Tukey HSD test and results showed that the 5 gram concentration exhibited the lowest average colony count among all groups and revealed a significant difference (p < 0.05) between the 5 gram group and both control groups. The 5 gram brewed had the highest antibacterial effect among the test groups, although it did not surpass the effectiveness of 0.2% chlorhexidine. Further studies recommended using different bacterial strains, MIC and MBC tests, specialized equipment for Total Plate Count analysis and in vivo studies are also necessary.